'Hic est vere Martyr, qui pro Christi nomine sanguinem suum fudit': representations and reflections of violence and suffering in the responsoria prolixa of saints' offices in the 'Codex Hartker'. Issue 1 (26th February 2014) - VAN BETTERAY, DIRK
ABSTRACT This article aims to show the relevance of musical and musical-textual analysis of saints' offices in approaching socio-historical aspects of the Middle Age. It investigates the moral and socio-historical concepts conveyed by the responsoria prolixa in honour of martyred saints in the famous Codex Hartker (CH-SGs 390–391, c.1000). What were the right ways to deal with violence and suffering? Did these differ for men, women and children? In the analysis of responsories in honour of St Stephen, St Lawrence, the Holy Innocents, Sts Cecilia and Agatha, striking musical or textual-musical features which emphasise or even interpret the message of the text have repeatedly been found. The quantity and similarity of such observations lifts them out of the haze of arbitrariness Indeed, it is possible to identify gender-specific and role-specific differences with regard to the behaviours which enabled people to attain the degree of sainthood.